2020
DOI: 10.1096/fj.201903044r
|View full text |Cite
|
Sign up to set email alerts
|

Modification of pore‐wall in direct ink writing wollastonite scaffolds favorable for tuning biodegradation and mechanical stability and enhancing osteogenic capability

Abstract: Surface chemistry and mechanical stability determine the osteogenic capability of bone implants. The development of high‐strength bioactive scaffolds for in‐situ repair of large bone defects is challenging because of the lack of satisfying biomaterials. In this study, highly bioactive Ca‐silicate (CSi) bioceramic scaffolds were fabricated by additive manufacturing and then modified for pore‐wall reinforcement. Pure CSi scaffolds were fabricated using a direct ink writing technique, and the pore‐wall was modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…107 For example, hydrogels will lose humidity if it is not preserved in a wet environment, 126 while harder materials like bioceramics or synthetic polymers can be degraded by mechanical forces, temperature, or flow shear. 162 The degradation rate is usually measured by mass loss tests after drying periods or enzymatic treatments. In ref 168, they used the eq XIII to calculate the remaining bulk hydrogel at certain time points after being incubated in phosphate buffered saline (PBS):…”
Section: Evaluation Of Porous Scaffoldsmentioning
confidence: 99%
“…107 For example, hydrogels will lose humidity if it is not preserved in a wet environment, 126 while harder materials like bioceramics or synthetic polymers can be degraded by mechanical forces, temperature, or flow shear. 162 The degradation rate is usually measured by mass loss tests after drying periods or enzymatic treatments. In ref 168, they used the eq XIII to calculate the remaining bulk hydrogel at certain time points after being incubated in phosphate buffered saline (PBS):…”
Section: Evaluation Of Porous Scaffoldsmentioning
confidence: 99%
“…Most non-organic doping involved magnesium [ 67 , 69 , 70 , 71 , 72 ], while others included copper [ 44 ], strontium [ 66 ] or graphene [ 68 ]. All of the studies reported an improvement in bone regeneration associated with loaded materials compared to their controls.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, due to the addition of the organic porogen, the controllable high-density micropores could be introduced into the shell layer after sintering, which helped in tuning the biodegradable properties of bioceramic scaffolds. Ke et al [192] fabricated highly bioactive Wollastonite scaffolds and then modified with magnesium (Mg) doping for pore-wall reinforcement. The modified scaffolds demonstrated better compressive strength than the unmodified ones while being favorable for retarding biodissolution and mechanical decay of scaffolds in vitro.…”
Section: Bioceramicsmentioning
confidence: 99%
“…Elsayed et al [190] Zn/Sr doped Wollastonite-diopside Porous architecture with limited strength decay and favorable bioactive ion release in bioceramic composites Bone repair and bone regenerative medicine applications Shen et al [191] Mg-doped wollastonite High compressive strength > 20 MPa with over 60% porosity Bone implants, clinical treatment of large bone defects, and bone tissue regeneration Ke et al [192] Mg-doped wollastonite Considerable initial flexural strength (31 MPa) and significant osteogenic capability…”
Section: Bone Tissue Engineering and Biomechanical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation